Do environmental performance and disclosure bring financial outcome? Evidence from Indonesia. (2019) - Devie, Devie; Kamandhanu, Jessica; Tarigan, Josua; Hatane, Saarce Elsye
In some developing countries such as Indonesia, there is a lack of regulatory controls in social responsibility performance and disclosure. Therefore, this paper is conducted to study the level of social responsibility performance and disclosure, as well as to investigate the relationship of environmental performance with a financial outcome, using environmental disclosure as the mediation variable. A firm's environmental performance is measured by PROPER score and the environmental disclosure with GRI index. Results show that firms' financial outcome is significantly affected by their environmental action (PROPER score and GRI Index). However, the findings also indicate that both environmental disclosure and profitability together are able to mediate the relationship between environmental performances and firms. The findings suggest that, in general, the majority of firms need to follow the GRI guidelines for reporting environmental information; therefore the investors should consider this information when making investment decisions.